GAMBARAN SURGICAL APGAR SCORE (SAS) PERIOPERATIF PADA PASIEN LAPARATOMI DI RUANG INSTALASI BEDAH SENTRAL RUMAH SAKIT UMUM DAERAH AJIBARANG - Edi Wibowo; Made Suandika; Martyarini Budi (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
Post-laparotomy complications include bleeding, severe pain, and even death. This can be reduced by effective perioperative management. One of them is by applying the Surgical Apgar Score (SAS) which contains hemodynamic information and intraoperative blood loss. The aim of the study was to determine perioperative SAS in laparotomy patients. Using a cross-sectional descriptive research design, this study took 21 respondents with quota sampling technique. The research instrument uses the SAS assessment sheet with data analysis using a frequency distribution. The results showed that most of the sample characteristics were late elderly (> 55 years) (28.6%) with female gender (66.7%). More than half of the sample (76.2%) had an SAS score in the moderate risk category. While the highest rates of morbidity and mortality (7/21) at 12.2% and 1.9%. The most SAS scores in laparotomy patients were in the moderate risk category.